KREATIVITAS GURU KELAS DALAM PEMANFAATAN MEDIA PEMBELAJARAN PADA MASA PANDEMI COVID-19 DI KELAS IV A SD ISLAM AL MADINA - Firsa Ulfiana; Ulya Himawati; Ersila Devy Rinjani (Magistra, 2022)
When learning occurs, teachers must be creative in developing learning media. Educators must be creative when delivering material via learning media. Schools have made efforts to foster teacher creativity, and various support facilities have been made available. Teachers face a variety of challenges as a result of online learning. This study focuses on classroom teachers' creativity, teacher constraints, and the school's efforts to use learning media during the COVID-19 pandemic. This is a field study with a qualitative approach. The study's findings indicate that (1) teachers' creativity in using interesting learning media will increase students' interest in learning. Virtual learning is the method employed. The media used is software-generated media, specifically the zoom application, YouTube, PPT, Whatsapp group, Google Classroom, Google Meet, Google Drive, and video call. The media used is then varied to create interesting and educational learning media. (2) The teacher's impediment to creating learning media during the COVID-19 pandemic class IV The network signal is Al Madina Islamic Elementary School, and the network plays an important role in teaching and learning activities. The first challenge for teachers when teaching online is network dependence. Second, student needs are not met during online learning. Third, there is a lack of parental supervision when engaging in online learning. (3) The school's efforts to develop teacher creativity include the provision of facilities and infrastructure that can be used without regard for space or time constraints, as well as an increase in the speed of the internet network in schools. The school conducts teacher evaluations. Following that is a workshop activity with the goal of expanding teachers' knowledge of teaching and developing creativity so that they can always improve themselves